2012
DOI: 10.1097/mpg.0b013e3182617c16
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Separation and C‐reactive Protein Elevation in Treatment‐naïve Pediatric Granulomatous Crohn Disease

Abstract: Objectives In patients with inflammatory bowel diseases (IBD), the presence of non-caseating mucosal granuloma is sufficient for diagnosing Crohn disease (CD) and may represent a specific immune response or microbial-host interaction. The cause of granulomas in CD is unknown and their association with the intestinal microbiota has not been addressed with high-throughput methodologies. Methods The mucosal microbiota from three different pediatric centers was studied with 454 pyrosequencing of the bacterial 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 48 publications
0
41
1
Order By: Relevance
“…Stenotrophomonas sp. and Eubacterium contortum are gut microbes found in ulcerative colitis, IBD, Crohn's disease, and nonalcoholic fatty live disease (37)(38)(39). We identified Stenotrophomonas species at day 45 in control females with a Ͼ1.0-fold difference compared to males, and males revealed a Ͻ1.0-fold increase compared to females; at every time point, this species appeared to increase in females with M. avium subsp.…”
Section: Differences In Immune Response By Females Versus Males Il-1␣mentioning
confidence: 90%
See 1 more Smart Citation
“…Stenotrophomonas sp. and Eubacterium contortum are gut microbes found in ulcerative colitis, IBD, Crohn's disease, and nonalcoholic fatty live disease (37)(38)(39). We identified Stenotrophomonas species at day 45 in control females with a Ͼ1.0-fold difference compared to males, and males revealed a Ͻ1.0-fold increase compared to females; at every time point, this species appeared to increase in females with M. avium subsp.…”
Section: Differences In Immune Response By Females Versus Males Il-1␣mentioning
confidence: 90%
“…Analysis of gut microbiota from pediatric Crohn's disease patients demonstrated that reductions in Roseburia were common in granulomatous disease; in our data, we observed a decrease in Roseburia with M. avium subsp. paratuberculosis infection over time, though Roseburia was nearly exclusively more abundant in females than in males (37). Stenotrophomonas sp.…”
Section: Differences In Immune Response By Females Versus Males Il-1␣mentioning
confidence: 99%
“…Additionally, the treatment-naïve nature of the examined samples is unique compared with any other epigenomic study on mucosal DNA in relationship to IBD thus far. Geographical bias can also complicate multi-center studies on flexible biological systems involved in IBD pathogenesis 23 . Our validation cohort contained samples from a single center eliminating this potential confounding factor.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,13 Since age, 22 IBD phenotype, 6 sample type, 22 geographic location, 24 and medications 20 can independently alter microbiome composition, a limited number of studies have included similar patients to facilitate comparisons. 8,10,21 These studies, from adult and pediatric populations, also used mucosal samples taken prior to treatment and consistently showed no differences in a diversity.…”
Section: Discussionmentioning
confidence: 99%